The limits of ethics in international relations natural law, natural rights, and human rights in transition - Boucher, David 1951- (Oxford Univ. Press, 2009)
David Boucher surveys the history of thinking about human rights and shows that far from being seen as universal and emancipatory, they have almost always privileged certain groups in relation to others.